A comparative study on teachers' attitudes towards inclusive education in Slovenia, Lithuania, and Finland - Murtonen, Carita (2020)
Inclusive education is an evolving ideological and practical change in the education sector globally. Teachers’ attitudes and commitment to inclusive education has an important role. Inclusive education is a context-related phenomenon, and for successful national-level implementation, national differences and needs have to be acknowledged. This research studied 1067 teachers in Finland, Lithuania and Slovenia comparing their attitudes towards inclusive education using Sentiments, Attitudes and Concerns in Inclusive Education (SACIE) scale and investigated background factors’ relation to the attitudes in each country. Differences between the teachers, divided by teaching experience, was studied in order to understand if any societal, political, and historical changes influence teachers’ attitudes. Data were analysed by using M/ANOVA and forced linear regression analysis. Results showed that there are differences in teachers attitudes towards inclusive education between the countries. Background factors related to Sentiments, Attitudes and Concerns varied in each country. In Lithuania, results indicated attitudinal changes, the younger generation being more positive towards inclusive education. Results provide tools to plan specific actions in each country for the successful implementation of inclusive education. In the future, mixed-method research analysis will provide more in-depth information as well as the comparison of countries with different income level. In order to understand better teachers’ attitudes in these countries, an additional study on the influence of efficacy and social norms would be beneficial.